2021
DOI: 10.3390/ijms222413408
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts in Pancreatic Ductal Adenocarcinoma: An Update on Heterogeneity and Therapeutic Targeting

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a leading cause of cancer-related morbidity and mortality in the western world, with limited therapeutic strategies and dismal long-term survival. Cancer-associated fibroblasts (CAFs) are key components of the pancreatic tumor microenvironment, maintaining the extracellular matrix, while also being involved in intricate crosstalk with cancer cells and infiltrating immunocytes. Therefore, they are potential targets for developing therapeutic strategies against PDAC. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 124 publications
1
42
0
Order By: Relevance
“…PSCs have long been considered a principal source of CAFs in PDACs. However, previous studies in various tumor types have indicated multiple cell origins for CAFs, including resident fibroblasts, bone marrow-derived mesenchymal stem cells, adiposederived stem cells, mesothelial cells, endothelial cells, and epithelial cells [90,[100][101][102][103][104]. A recent study has suggested a pro-tumorigenic contribution of PSC-derived CAFs, although PSC-derived CAFs are a minor subset of the total CAFs present in PDAC tissues [105].…”
Section: Caf Originsmentioning
confidence: 99%
“…PSCs have long been considered a principal source of CAFs in PDACs. However, previous studies in various tumor types have indicated multiple cell origins for CAFs, including resident fibroblasts, bone marrow-derived mesenchymal stem cells, adiposederived stem cells, mesothelial cells, endothelial cells, and epithelial cells [90,[100][101][102][103][104]. A recent study has suggested a pro-tumorigenic contribution of PSC-derived CAFs, although PSC-derived CAFs are a minor subset of the total CAFs present in PDAC tissues [105].…”
Section: Caf Originsmentioning
confidence: 99%
“…Therefore, there existed discrepancies between the results obtained using cultured PSCs and those obtained by Hedgehog inhibitors or targeting α -SMA in genetically engineered mouse models. It is also noteworthy that the several clinical trials assessing the effectiveness of PSC-targeting therapies failed to show effectiveness ( Vaish et al, 2021 ). The clinical trial evaluating efficacy of IPI-926 with gemcitabine has been halted due to unexpected shortening of survival in patients with advanced pancreatic cancer, who received combination therapy.…”
mentioning
confidence: 99%
“…[571,576] These studies had the double effect of improving PDAC therapy by enhancing drug delivery into the tumor site while elucidating the complex and dual role of CAFs in desmoplasia. [577] They involved, among many other mechanisms, [503] the use of polymeric micelle-based nanoformulations to inhibit SHH pathway, [576] nab-paclitaxel to target SPARC glycoprotein, [578] miRNA inhibitors to reprogram CAFs, [579] and anti-microRNA as part of peptide-based nanocomplexes aimed at inhibiting PSC differentiation into CAFs. [580] PSCs, as stated above, are the main responsible for the increased ECM production which ultimately provokes reduced intratumoral perfusion and nanotherapeutic delivery.…”
Section: Targeted/stromal Therapiesmentioning
confidence: 99%